The search for ‘Ichambawilo’ (an encounter) with refugee and asylum-seeker parents whose children are vulnerable: an African Drama therapy intervention programme - Busika, Nonkululeko Faith (University of the Witwatersrand, Johannesburg, 2024)
Refugees and asylum-seeker parents in South Africa usually find it difficult to adequately fulfil their parental responsibilities because they face many challenges. ‘Three2Six’ is a project in Johannesburg, which focuses on refugee and asylum-seeker children’s right to education and psycho-social well-being. I, as a drama therapist, have personally observed that drama therapy makes a meaningful contribution to the ‘Three2Six project’ because it assists teachers to address the therapeutic needs of refugee and asylum-seeking children who are manifesting psychosocial and behavioural problems at school. Unfortunately, the parents of the children I rendered drama therapy to did not seem to be able to help their children make good progress. The main purpose of the study was thus to design an African Drama Therapy intervention programme with the ‘Three2Six’ parents so that they could adequately fulfil their parental responsibilities. The need to engage the parents of these learners increased even more because the COVID-19 pandemic encouraged children to be at home. The research methods selected to fulfil the study's main purpose was action research in the field of Drama Therapy. The study used multiple approaches in three different phases. Participants were purposively selected and included the parents and school staff members at the Holy Family College and Sacred Heart College, where the Three2Six project is housed. The main theoretical and conceptual frameworks underlying the research were Moreno’s Role theory, the concept of African spirituality and Ubuntu. Data were gathered during the three phases of the research process by conducting personal, semi-structured interviews with school staff members and a Visual Mapping discussion with parent participants using drama therapy techniques, role embodiment and a recorder. The study findings are an African Drama Therapy Intervention programme, (the API-R5), that takes into consideration Ubuntu and Spirituality being central to African well-being. The findings further demonstrate how the Western approach to Drama Therapy, can be adapted to the African context
A research report Submitted in fulfillment of the requirements for a Doctor of Philosophy in Drama Therapy, In the Faculty of Humanities , School of Arts, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; drama therapy; intervention programme; parenting; vulnerable children; psychosocial well-being; encounter / Ichambawilo; SDG-4: Quality education